The Influence of Solvency, Profitability, and Size of KAP on Audit Delay 2017-2019 Period - Adhie Maston Munthe (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
The report of a financial statement is a description of a corporation's performance, without the existence of financial reports, users of financial statements such as owners, company management, investors, and others cannot know the development of the company. Although financial reports are very necessary and useful, there are still many companies that are late in providing their financial reports (Audit Delay). This research was conducted to determine the factors that form financial statements such as solvency, profitability, and size of the public accounting firm (KAP) that affect the occurrence of audit delay. The technique used in this study is a quantitative research method so that a sample of 90 financial reports can be obtained from 30 banking companies that provide their financial reports continuously from 2017 to 2019.